تأثير زمن التلبيد الحراري على الكثافة الظاهرية والأبعاد النهائية للمدمج المنتج بتقانة المساحيق المعدنية - تفاحة, منهل; معلا, معلا (Latakia University Journal -Engineering Sciences Series, 2017)
دُرِسَ في هذا البحث مجموعة من التجارب لعملية تدميج (Compacting) عدة مساحيق معدنية (Powder Metal) تشكل خليطة معدنية من مادة المساحيق ذات الأساس الحديدي لشكل هندسي أسطواني، وتم القيام بعدة اختبارات من أجل الوصول إلى العلاقة التي تربط الكثافة الظاهرية النهائية للمدمج مع زمن التلبيد الحراري، ودراسة مدى تغير الأبعاد الهندسية للمدمج النهائي بعد الانتهاء من عملية التلبيد الحراري خلال فترات زمنية مختلفة.بينت نتائج الاختبارات والقياسات أن زمن التلبيد الحراري يؤثر بشكلٍ إيجابي على الكثافة الظاهرية للمدمج النهائي المصنع بتقانة المساحيق المعدنية، وبالتالي ستزداد متانته، حيث التناسب يكون طردياً حتى الوصول إلى حد معين. وأيضاً تأثيره كان واضحاً على تقلص أقطار العينات المستخدمة في الاختبارات. وتغير (زيادة ونقصان) في ارتفاع العينات.أظهرت نتائج البحث الأهمية الكبيرة لمتابعة دراسة وتحليل العلاقات التي تربط متغيرات تقانة تدميج المساحيق المعدنية مع بعضها البعض، وتأثيراتها المختلفة على المدمج النهائي الناتج.In this search, has been studied set of practical experiences for compacting several metal powders composed a metallic alloy based iron from powders with a proposed geometric shapes (cylindrical). Several tests were done in order to reach the relationship between the final apparent density for the compact with a sintering time, and study changing the geometric dimensions of the final compact after the completion of sintering process during different time periods. The tests and Measurement results had been demonstrated that sintering time affect positively on the apparent density of the final compact which Manufactured by technique metal powders, and thus will increase its strength, where proportionality is directly proportional access even to a certain extent. And also its effect was an obvious shrinking diameters samples used in the tests. And changing (increase or decrease) in height samples. Search has shown the great importance of the follow-up studying and analyzing the relationships which associate that variables of metal powders technique each other, and their different effect on the final compact.